Three-dimensional modelling of Ge1-xSix by the travelling solvent method in the presence of coriolis and centrifugal forces. (1st December 2004) - Makriyannis, T.J.; Saghir, M.Z.; Labrie, D.
The travelling solvent method known as TSM is a process used to produce pure and homogeneous crystals. The TSM process has been tested on many alloys producing uniform and uncontaminated crystal products. A three-dimensional numerical simulation for the fluid flow, heat and mass transfer in the solvent during the growth of Ge1-x Six by the travelling solvent method under axial rotation has been modelled. The full Navier-Stokes equations together with the energy, mass transport and continuity equations were solved numerically using the finite element technique. The application of crucible rotation to the travelling solvent method is an attempt to control the buoyancy induced convection throughout the melt and to suppress the three-dimensional characteristics of unsteady heat flow. The application of rotation was shown to have a considerable effect on the buoyancy-induced flow. An optimal rotational speed was found that lessened the convective flow, provided a uniform concentration along the growth interface, and gave symmetrical characteristics to the three-dimensional buoyancy-induced flow.